1972
DOI: 10.1111/j.1471-0528.1972.tb12921.x
|View full text |Cite
|
Sign up to set email alerts
|

Ctstine Aminopeptidase in Normal and Complicated Pregnancies

Abstract: Summary Normal values for serum cystine aminopeptidase (CAP) during pregnancy are established and compared with results from abnormal pregnancies. Steadily rising CAP values suggest adequate lacental function. A correlation exists between the final CAP value and birthweight in normal pregnancies. The implications of various trends in CAP results in abnormal pregnancies are considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1973
1973
1989
1989

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Several authors have found an association between birth-weight and matemal serum levels of hCS, estriol and oxytocinase [l, 8,10,11,12,14,15,16,17,18,20,21,22,23,25,28]. However, this association was not confirmed by others [4,6,7,19,27].…”
Section: Discussionmentioning
confidence: 43%
“…Several authors have found an association between birth-weight and matemal serum levels of hCS, estriol and oxytocinase [l, 8,10,11,12,14,15,16,17,18,20,21,22,23,25,28]. However, this association was not confirmed by others [4,6,7,19,27].…”
Section: Discussionmentioning
confidence: 43%
“…The levels in patients with essential hypertension were below 4-8. This difference from patients with preeclamptic toxaemia has been shown with serum levels of 3-glucuronidase (McDonald and Odell, 1947), cystine aminopeptidase (Hurry et al, 1972), and, to a lesser degree, uric acid (Pollak and Nettles, 1960).…”
Section: Discussionmentioning
confidence: 92%
“…It has suggested that plasma oestriol values would be more useful for determining feto-placental viability than the corresponding urinary measurement (69-71). Although previous studies have shown correlation between the urinary oestrogen levels and the serum cystyl-amino peptidase activity (21,22,28,29,(72)(73)(74), it is not well understood with respect to the relationship between the serum cystyl-amino peptidase activity and the plasma oestriol level. In this study, therefore, the plasma oestriol level and the cystyl-amino peptidase activity with various substrates were studied simultaneously in pregnancy.…”
Section: Discussionmentioning
confidence: 98%
“…Serial serum cystyl-amino peptidase estimations appear to be helpful in the diagnosis of placental failure (17)(18)(19)(20) and the management of intrauterine fetal growth retardation and fetal distress, etc (21)(22)(23)(24)(25)(26)(27), but there is some controversy (28)(29)(30)(31)(32). This may be the consequence of differences in various methods used for the enzymes assay.…”
Section: Introductionmentioning
confidence: 94%